2020
DOI: 10.1126/scitranslmed.aau2939
|View full text |Cite
|
Sign up to set email alerts
|

PET ligands [ 18 F]LSN3316612 and [ 11 C]LSN3316612 quantify O -linked-β- N -acetyl-glucosamine hydrolase in the brain

Abstract: We aimed to develop effective radioligands for quantifying brain O-linked-β-N-acetyl-glucosamine (O-GlcNAc) hydrolase (OGA) using positron emission tomography in living subjects as tools for evaluating drug target engagement. Posttranslational modifications of tau, a biomarker of Alzheimer’s disease, by O-GlcNAc through the enzyme pair OGA and O-GlcNAc transferase (OGT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In addition, ∼90% of the [ 18 F]LSN3316612 is specifically bound to OGA, on the basis of blocking studies with Thiamet-G and the nonradioactive parent ligand. 333,334 Obviously, PET imaging with [ 18 F]LSN3316612 demonstrates its good brain uptake, a high percentage of specific and reversible binding, selectivity for its target OGA in vivo, and amenability to quantitation with compartmental modeling. Further studies reveal that [ 18 F]LSN3316612 is an excellent PET radioligand for imaging and quantifying OGA in the brain of healthy human participants (Figure 5).…”
Section: Basics Of Ogamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ∼90% of the [ 18 F]LSN3316612 is specifically bound to OGA, on the basis of blocking studies with Thiamet-G and the nonradioactive parent ligand. 333,334 Obviously, PET imaging with [ 18 F]LSN3316612 demonstrates its good brain uptake, a high percentage of specific and reversible binding, selectivity for its target OGA in vivo, and amenability to quantitation with compartmental modeling. Further studies reveal that [ 18 F]LSN3316612 is an excellent PET radioligand for imaging and quantifying OGA in the brain of healthy human participants (Figure 5).…”
Section: Basics Of Ogamentioning
confidence: 99%
“…Further studies reveal that [ 18 F]LSN3316612 is an excellent PET radioligand for imaging and quantifying OGA in the brain of healthy human participants (Figure 5). 334,335 Even though only limited examples have emerged so far, apparently PET imaging with radioactive inhibitors to OGA have already demonstrated its great strength. On one hand, it will assist our understanding of OGA in vivo and aid the exploration of pathophysiology (e.g., the distribution of OGA in subjects at baseline and perturbation, by using whole-body PET scanning).…”
Section: Basics Of Ogamentioning
confidence: 99%
“…Initially, the [ 3 H]LSN3316612 was used to image and quantify OGA in the brains of living subjects like rats, monkeys, and humans, and later the [ 18 F]LSN3316612 was used to image OGA in vivo with the blocking agent thiamet G in monkeys. Furthermore, the research has been extended and reported the PET quantification of O-GlcNAcase in the brain of healthy human volunteers using [ 18 F]LSN3316612, the V T was calculated with two tissue compartment model, and also reported Region-based as well as voxel-based quantification of [ 18 F]LSN3316612 in the human brain for O-GlcNAcase ( 122 , 123 ). Zhang et al have discovered a novel Radioligand PF-06445974 to image preferably Phosphodiesterase (PDE) 4B-isoform using PET, which is this cold ligand had shown promising results with high potency and selectivity over PDE-4D isoform.…”
Section: Novel 18 F and 11 C-ra...mentioning
confidence: 99%
“…Other animal species are also used to evaluate PET radiopharmaceuticals. For example, rhesus monkeys are commonly used to evaluate neuro-PET radiopharmaceuticals with respect to target engagement, distribution, and dosimetry [235].…”
Section: Dosimetrymentioning
confidence: 99%